Determination in village financial governance during the COVID-19 pandemic - Rimky Mandala Putra Simanjuntak; Duma Megaria Elisabeth; Sahala Purba; Santy Sitohang; Novita Tarigan (Jurnal Akuntansi Aktual, 2023)
AbstractThe purpose of this research is to examine the relationship between accountability, transparency, and understanding of the village officials in village financial governance during the COVID-19 pandemic in villages around Biru-Biru District, Deli Serdang Regency. This quantitative research used primary data collected from a questionnaire survey in 17 villages in Biru-Biru District, Deli Serdang Regency, from January to March 2022. The samples consisted of the village chief, the secretary, and the head of finance. In total, the respondents were 51. The results of this research indicate that accountability and understanding of village officials have a positive and significant effect on the village’s financial management, but transparency has a negative effect on village financial governance. Therefore, a good understanding from the village officials will improve village financial management and fulfill the expectations of the central government to advance the economy of Indonesian rural communities, especially during the COVID-19 pandemic.AbstrakTujuan penelitian ini adalah untuk memeriksa hubungan antara akuntabilitas, transparansi, dan pemahaman pejabat desa dalam pengelolaan keuangan desa selama pandemi COVID-19 di desa-desa di sekitar Distrik Biru-Biru, Deli Serdang Regency. Penelitian kuantitatif ini menggunakan data primer yang dikumpulkan dari survei kuesioner di 17 desa di Distrik Biru-Biru, Deli Serdang Regency, dari Januari hingga Maret 2022. Sampel terdiri dari kepala desa, sekretaris, dan kepala keuangan. Total responden adalah 51. Hasil penelitian ini menunjukkan bahwa akuntabilitas dan pemahaman pejabat desa memiliki efek positif dan signifikan pada manajemen keuangan desa, tetapi transparansi memiliki efek negatif pada pemerintahan keuangan desa. Oleh karena itu, pemahaman yang baik dari para pejabat desa akan meningkatkan manajemen keuangan desa dan memenuhi harapan pemerintah pusat untuk memajukan perekonomian masyarakat pedesaan Indonesia, terutama selama pandemi COVID-19.